2011
DOI: 10.1037/a0021614
|View full text |Cite
|
Sign up to set email alerts
|

The world is not flat: Can people reorient using slope?

Abstract: Studies of spatial representation generally focus on flat environments and visual input. However, the world is not flat, and slopes are part of most natural environments. In a series of 4 experiments, we examined whether humans can use a slope as a source of allocentric, directional information for reorientation. A target was hidden in a corner of a square, featureless enclosure tilted at a 5° angle. Finding it required using the vestibular, kinesthetic, and visual cues associated with the slope gradient. In E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
84
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(91 citation statements)
references
References 56 publications
5
84
2
Order By: Relevance
“…Other elements in addition to geometry and features may need to be added. For example, the slope of the arena floor has been shown to be an important cue, often more important than geometric cues in conflict situations for pigeons (Nardi & Bingman, 2009;Nardi, Nitsch, & Bingman, 2010), and slope is also used by humans, although possibly less consistently (Nardi, Newcombe, & Shipley, 2011). The cast of elemental pieces is crucial to predicting how the agent would behave in various kinds of transformed spaces-for example, when a rectangle is elongated or made into a square or trapezoid.…”
Section: Critiquementioning
confidence: 99%
“…Other elements in addition to geometry and features may need to be added. For example, the slope of the arena floor has been shown to be an important cue, often more important than geometric cues in conflict situations for pigeons (Nardi & Bingman, 2009;Nardi, Nitsch, & Bingman, 2010), and slope is also used by humans, although possibly less consistently (Nardi, Newcombe, & Shipley, 2011). The cast of elemental pieces is crucial to predicting how the agent would behave in various kinds of transformed spaces-for example, when a rectangle is elongated or made into a square or trapezoid.…”
Section: Critiquementioning
confidence: 99%
“…In particular, pigeons use a uniform, sloping floor to reorient, even if other cues, such as the shape of the environment, are available (Nardi & Bingman, 2009) and are better predictors of the goal location (Nardi et al, 2010). The strong reliance on slope gradients is probably related to the increased effort of moving on inclines, and to the fact that navigating on tilted surfaces creates a multimodal sensory experience, as slope is simultaneously perceived by visual, kinesthetic, and vestibular receptors.Despite the strong reliance on slope exhibited by nonhuman animals, the only human study on terrain slope reorientation carried out in a real environment showed surprising variability in performance, with a large percentage of the participants being unable to notice the incline and use it to locate a hidden goal (Nardi, Newcombe, & Shipley, 2011). Sex was found to be related to these individual differences, with men showing a performance advantage of 1.4 SDs over women-an effect size larger than that reported in most studies of mental rotation, a spatial skill characterized by large sex-related differences (Voyer, Voyer, & Bryden, 1995).…”
mentioning
confidence: 99%
“…However, the beneficial effect of slant on navigation could be due to changes in the underlying structure of spatial memory or changes in spatial orientation in the presence of environmental slant. The usefulness of slant as a cue to spatial orientation has previously been established (Chai & Jacobs, 2010;Nardi et al 2010Nardi et al , 2011. However, the influence of environmental slant on spatial memory organization has been relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Both tasks required participants to determine their current position and orientation within the virtual environment and then retrieve a remembered goal location relative to their position and orientation. There is ample evidence that environmental slant facilitates spatial orientation (Chai & Jacobs, 2010;Nardi, Newcombe, & Shipley, 2010, 2011, but comparatively little evidence that slope influences the organization of spatial memories.…”
mentioning
confidence: 99%